Discovery of plastic-degrading microbial strains isolated from the alpine and Arctic terrestrial plastisphere - Rüthi, Joel; Cerri, Mattia; Brunner, Ivano; Stierli, Beat; Sander, Michael; Frey, Beat (Frontiers in Microbiology, 2023)
Increasing plastic production and the release of some plastic in to the environment highlight the need for circular plastic economy. Microorganisms have a great potential to enable a more sustainable plastic economy by biodegradation and enzymatic recycling of polymers. Temperature is a crucial parameter affecting biodegradation rates, but so far microbial plastic degradation has mostly been studied at temperatures above 20°C. Here, we isolated 34 cold-adapted microbial strains from the plastisphere using plastics buried in alpine and Arctic soils during laboratory incubations as well as plastics collected directly from Arctic terrestrial environments. We tested their ability to degrade, at 15°C, conventional polyethylene (PE) and the biodegradable plastics polyester-polyurethane (PU; Impranil®); ecovio® and BI-OPL, two commercial plastic films made of polybutylene adipate-co-terephthalate (PBAT) and polylactic acid (PLA); pure PBAT; and pure PLA. Agar clearing tests indicated that 19 strains had the ability to degrade the dispersed PU. Weight-loss analysis showed degradation of the polyester plastic films ecovio® and BI-OPL by 12 and 5 strains, respectively, whereas no strain was able to break down PE. NMR analysis revealed significant mass reduction of the PBAT and PLA components in the biodegradable plastic films by 8 and 7 strains, respectively. Co-hydrolysis experiments with a polymer-embedded fluorogenic probe revealed the potential of many strains to depolymerize PBAT. Neodevriesia and Lachnellula strains were able to degrade all the tested biodegradable plastic materials, making these strains especially promising for future applications. Further, the composition of the culturing medium strongly affected the microbial plastic degradation, with different strains having different optimal conditions. In our study we discovered many novel microbial taxa with the ability to break down biodegradable plastic films, dispersed PU, and PBAT, providing a strong foundation to underline the role of biodegradable polymers in a circular plastic economy.